Healthcare staff perceptions and misconceptions regarding antibody testing in the United Kingdom: implications for the next steps for antibody screening. (May 2021) - Robbins, T.; Kyrou, I.; Laird, S.; Morgan, N.; Anderson, N.; Imray, C.; Patel, K.; Sankar, S.; Randeva, H.; Jones, C.
Summary: Background: Healthcare workers have been at increased risk of exposure, infection and serious complications from COVID-19. Antibody testing has been used to identify staff members who have been previously infected by SARS-CoV-2, and has been rolled out rapidly in the United Kingdom. A number of comment and editorial articles have been published that raise concerns about antibody testing in this context. We present perceptions of National Health Service (NHS) healthcare workers in relation to SARS-CoV-2 antibody testing. Methods: An electronic survey regarding perceptions towards SARS-CoV-2 antibody testing was distributed to all healthcare workers at a major NHS tertiary hospital following implementation of antibody testing. Results: In total, 560 healthcare workers completed the survey (80% female; 25% of Black and Minority Ethnic background; 58% from frontline clinical staff). Exploring whether they previously had COVID-19 was the primary reported reason for choosing to undergo antibody testing (85.2%). In case of a positive antibody test, 72% reported that they would feel relieved, whilst 48% felt that they would be happier to work in a patient-facing area. Moreover, 12% responded that a positive test would mean "social distancing is less important", with 34% of the responders indicating that in this case they would be both less likely to catch COVID-19 and happier to visit friends/relatives. Conclusions: NHS staff members primarily seek out SARS-CoV-2 antibody testing for an appropriate reason. Based on our findings and given the lack of definite data regarding the extent of immunity protection from a positive SARS-CoV-2 antibody test, significant concerns may be raised regarding the reported interpretation by healthcare workers of positive antibody test results. This needs to be further explored and addressed to protect NHS staff and patients.